Improving the Innate Immune Response in Diabetes by Modifying the Renin Angiotensin System - Soto, Maira; Gaffney, Kevin J.; Rodgers, Kathleen E. (Frontiers in Immunology, 2019)
Patients with Type 2 Diabetes Mellitus (T2DM) suffer from a higher incidence and severity of pulmonary infections. This is likely due to immune impairment and structural abnormalities caused by T2DM-induced oxidative stress (OS) and chronic inflammation. Modulation of the Renin Angiotensin System (RAS) through blockade of the actions of angiotensin II (AII), or inducing the protective pathway, has the potential to reduce these pathological pathways. The effects of Angiotensin 1-7 [A(1-7)] and NorLeu3-A(1-7) [NorLeu], ligands of the protective RAS, on the innate immune response were evaluated in the db/db mouse model of T2DM. Only NorLeu treatment reduced the structural pathologies in the lung caused by T2DM. A decreased in bactericidal activity and phagocytosis in diabetic animals was also observed; both A(1-7) and NorLeu treatment restored these functions. Myeloid progenitor CFUs were reduced and neutrophil/progenitor OS was increased in saline-treated db/db mice, and was reversed by A(1-7) and NorLeu treatment. These results demonstrate the adverse effects of diabetes on factors that contribute to pulmonary infections and the therapeutic potential of protective RAS peptides. Overall, RAS-modification may be a viable therapeutic target to treat diabetic complications that are not addressed by glucose lowering drugs.